2020
DOI: 10.1016/j.mex.2020.101152
|View full text |Cite
|
Sign up to set email alerts
|

A new method of interface tension measurement of a magnetic fluid drop

Abstract: A new method for determining the interfacial tension of a magnetic fluid (MF) is proposed on the basis of deformation of a MF drop lying on a liquid substrate and subjected to a vertical uniform magnetic field. The results show that the drop elongates in the direction of the field with an increase of its intensity. As soon as the field strength reaches a certain value, the interface and the free surface of the drop become unstable, which causes the peaks of different height to form. It has been found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Khokhryakova et al 109 (and also ref. 183) showed that both the peak-formation instabilities occur at different magnetic fields and that the ratio of these two critical field intensities was correlated to the measurement of the surface/interfacial tensions. We have previously explained the deformation dynamics of an FF droplet in this configuration 109 in relation to Fig.…”
Section: Applications Of Magnetic Field-mediated Sessile Droplet Shapingmentioning
confidence: 95%
See 2 more Smart Citations
“…Khokhryakova et al 109 (and also ref. 183) showed that both the peak-formation instabilities occur at different magnetic fields and that the ratio of these two critical field intensities was correlated to the measurement of the surface/interfacial tensions. We have previously explained the deformation dynamics of an FF droplet in this configuration 109 in relation to Fig.…”
Section: Applications Of Magnetic Field-mediated Sessile Droplet Shapingmentioning
confidence: 95%
“…For all the systems studied in both ref. 109 and 183, the first peak was formed at the submerged part of the FF droplet dispensed atop a liquid substrate, i.e. , deformation of the liquid–liquid interface, and followed by peak formation at the upper part, i.e.…”
Section: Applications Of Magnetic Field-mediated Sessile Droplet Shapingmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Indirectly, surface tension can be estimated by analyzing the spatial scale of this relief. 10,13,14 Another class of techniques is based on the analysis of the shape of a FF droplet suspended in a nonmagnetic liquid, or drop-like aggregates being a condensed phase of the surrounding FF. These droplets elongate in the external MF.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a transversely homogeneous MF this phenomenon results in the emergence of Rosensweig surface instability and the formation of a stationary topography . Indirectly, surface tension can be estimated by analyzing the spatial scale of this relief. ,, …”
Section: Introductionmentioning
confidence: 99%